CIMMYT continues to sustainably address global hunger - Joshi, Arun K.; Kropff, Martin (Indian Farming, 2018)
Given the challenges imposed by climate change, increasing population, dwindling resources and a range of socio-economic issues in the developing world, CIMMYT has made a significant contribution to the overall sustainability of food security and poverty reduction. To achieve the required productivity gains, strong emphasis on enhancing yield potential together with climate resilience, appropriate crop management and policy support must continue.